2023
DOI: 10.1111/cns.14442
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the nucleus tractus solitarius in the therapeutic effect of electroacupuncture on post‐stroke dysphagia through the primary motor cortex

Qiuping Ye,
Si Yuan,
Lulu Yao
et al.

Abstract: BackgroundPost‐stroke dysphagia (PSD), a common and serious disease, affects the quality of life of many patients and their families. Electroacupuncture (EA) has been commonly used effectively in the treatment of PSD, but the therapeutic mechanism is still under exploration at present. We aim to investigate the effect of the nucleus tractus solitarus (NTS) on the treatment of PSD by EA at Lianquan (CV23) through the primary motor cortex (M1).MethodsC57 male mice were used to construct a PSD mouse model using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…By comparing the effects of administering EA on CV23 and Neiguan (PC6), Ye QP et al found that administering EA on CV23 could regulate the swallowing function by activating swallowing-related interneurons in the ventrolateral medulla oblongata ( 37 ). In addition, in a recent study, Ye QP et al also demonstrated through optogenetics and chemogenetics that the NTS is involved in the regulation of EA on CV23 for PSD, revealing the role of the M1-NTS pathway in EA on CV23 ( 38 ). The latest research shows that in addition to the central nervous system, EA on CV23 can also have an impact on the peripheral nervous system and the local swallowing muscles.…”
Section: Discussionmentioning
confidence: 98%
“…By comparing the effects of administering EA on CV23 and Neiguan (PC6), Ye QP et al found that administering EA on CV23 could regulate the swallowing function by activating swallowing-related interneurons in the ventrolateral medulla oblongata ( 37 ). In addition, in a recent study, Ye QP et al also demonstrated through optogenetics and chemogenetics that the NTS is involved in the regulation of EA on CV23 for PSD, revealing the role of the M1-NTS pathway in EA on CV23 ( 38 ). The latest research shows that in addition to the central nervous system, EA on CV23 can also have an impact on the peripheral nervous system and the local swallowing muscles.…”
Section: Discussionmentioning
confidence: 98%
“…Two parts make up the pattern generator of the swallowing center: (1) the dorsal region consisting of the nucleus tractus solitarius and peripheral neurons; (2) the nucleus and reticular formation surrounding the nucleus are located in the ventral region ( Jang and Kim, 2021 ). Nucleus ambiguous innervates the muscles of the oral cavity, larynx, and pharynx through the trigeminal, facial, glossopharyngeal, vagus, and accessory nerves ( Petko and Tadi, 2023 ; Chandran and Doucet, 2024 ), The nucleus tractus solitary can receive incoming information from the nucleus doubtful and then send efferent fibers to the corresponding muscles, but mainly integrates information from higher cortical centers and peripheral sensory afferents and regulates swallowing according to the nature of the food bolus ( Chandran and Doucet, 2024 ; Ye et al, 2024 ). Overall (see Figure 1 ), the swallowing central pattern generator is responsible for the formation and regulation of swallowing motor sequences, processing incoming information, generating preprogrammed swallowing responses, and distributing appropriate signals to the motor nuclei of cranial nerves and their axons, which are ultimately transmitted to the many muscles involved in swallowing ( Yamamoto et al, 2022 ).…”
Section: Mechanisms Associated With Dysphagiamentioning
confidence: 99%
“…The nucleus tractus solitary can receive incoming information from the nucleus doubtful and then send efferent fibers to the corresponding muscles, but mainly integrates information from higher cortical centers and peripheral sensory afferents and regulates swallowing according to the nature of the food bolus (Chandran and Doucet, 2024;Ye et al, 2024). Overall (see Figure 1), the swallowing central pattern generator is responsible for the formation and regulation of swallowing motor sequences, processing incoming information, generating preprogrammed swallowing responses, and distributing appropriate signals to the motor nuclei of cranial nerves and their axons, which are ultimately transmitted to the many muscles involved in swallowing (Yamamoto et al, 2022).…”
Section: Mechanisms Associated With Dysphagiamentioning
confidence: 99%
“…The nucleus tractus solitary can receive incoming information from the nucleus doubtful and then send efferent fibers to the corresponding muscles, but mainly integrates information from higher cortical centers and peripheral sensory afferents and regulates swallowing according to the nature of the food bolus (Chandran and Doucet, 2024;Ye et al, 2024). Overall (see Figure 1), the swallowing central pattern generator is responsible for the formation and regulation of swallowing motor sequences, processing incoming information, generating preprogrammed swallowing responses, and distributing appropriate signals to the motor nuclei of cranial nerves and their axons, which are ultimately transmitted to the many muscles involved in swallowing (Yamamoto et al, 2022).…”
Section: Mechanisms Associated With Dysphagiamentioning
confidence: 99%